The evolving language of environmental protection in bilateral investment treaties, free trade agreements, and trade promotion agreements. Issue Volume 12:(2016)Special Issue (26th July 2018) - Webster, Timothy
Abstract : In this paper we focus on the use of the word 'environmental' in the context of two Free Trade Agreements between the US and Oman (2009), and Peru (2009). Since mention of the word 'environmental' in the Preambles of Bilateral Investment Treaties dating back to the early 1990s, references to environmental concerns have increasingly been incorporated into the articles of trade treaties and agreements. In the Bilateral Investment Treaties dating back to 1994 between the United States and the countries of Georgia and Trinidad and Tobago, mention of environmental concerns only appears in the Preamble. Although not strictly identified as the Preamble, but nevertheless preambular in nature, the BIT between the United States and Bolivia (1998) begins with a series of '-ing' clauses indicating the intentions of the two parties to the treaty. The penultimate clause repeats the trinity of concerns which one finds at the close of other BIT preambles to which the United States was a party: 'health, safety, and environmental measures'. With the turn of the century BITs began to give far greater attention to environmental concerns. The Preambles of the Chile-United States Free Trade Agreement (2003), the Dominican Republic-Central America- United States Free Trade Agreement (CAFTA-DR), as well as Trade Promotion agreements between the United States and Colombia, Peru, and Panama all state very similar intentions with respect to environmental concerns. Noteworthy are recent FTAs between the United States and Oman (2009) and Peru (2009). In both agreements, one chapter is completely devoted to the Environment. In this paper, we investigate the language used in these chapters and explore the implications for securing improved environmental protection. This chapter surveys the use of the word 'environmental' in BITs, FTAs (other than NAFTA), and TPAs, not only in terms of how and where mention occurs in the treaty/agreement text, but also identifying those disputes whose tribunal deliberation specifically took into account references to environmental concerns in a particular treaty/agreement, thereby providing some basis for assessing the impact these treaty/agreement references to environmental concerns may have had on tribunal decision making. The first part of this chapter looks at references to 'environmental' in BITs, followedby similar discussion of FTAs and TPAs. The sequencing in each part is chronological, showing how treaty/agreement provisions have been evolving. Since mention of the word 'environmental' in the Preambles of Bilateral Investment Treaties dating back to the early 1990s, references to environmental concerns have increasingly been incorporated into the articles of the treaties and agreements. The inclusion here of information about relevant disputes and tribunal deliberations and awards is highly relevant to making a realistic assessment of the impact of the inclusion of treaty/agreement language concerning environmental issues.There are indications that the pendulum is swinging away from Tribunal rulings favoring investments at the expense of environmental protection to more balanced rulings which take note of greater mention of environmental concerns in treaties and agreements.